O Programa Bolsa Família como estratégia de superação da insegurança alimentar e nutricional: estudo de coorte realizado em municípios do interior da Paraíba - Cabral, Caroline Sousa (2012)
Discussions involving Food and Nutrition Security (SAN) in Brazil has intensified since the beginning of the Lula government. Through the recreation of CONSEA, in 2004 occured the Second National Conference of Food and Nutrition Security. On this occasion, systematized the concept of SAN, which is understood by all citizens access to quality food in sufficient quantity, on a regular and permanent, so that other needs are not compromised by guaranteeing this right respecting cultural diversity, and sustainable from the standpoint of social, environmental and economic. The Bolsa Família Program (PBF) was created under the Fome Zero Strategy, in order to combat hunger and poverty and promote Food and Nutrition Security. This study aims to evaluate the impact of PBF in overcoming the Food Insecurity and Nutrition (IA). It was adopted as a selection criterion in the families interviewed prior survey, in 2005, since they were living in São José dos Ramos and Nova Floresta/PB. Initially 609 households were assessed, however, being withdrawn follow-up losses in 2011 were found and interviewed 406 families. We used Chi-square McNemar to examine longitudinal changes in categorical variables. To analyze continuous variables, comparing the two years, we used paired T Test. It was assumed α ≤ 0.05 for statistical significance. There was an increase of SAN/IA Mild over levels Moderate/Severe. Was diagnosed improvement in indicators that would reflect positively on the economic standard of the respondents, as per capita income, increased coverage and benefit value of PBF. We observed significant improvement in the situation SAN only in households that have managed to overcome poverty, allowing to infer causal relationship between increased income and food security. The situation of SAN/IA Mild increased in families that were included in the PBF in both instances, and in that they failed to receive the benefit later in 2005. The program has a positive impact on increasing income, supporting higher levels of SAN, but not the only factor influencing improvements in the economic profile of this population. During these six years of investment, the program has met its purpose. As increases the income of individuals, contributes to overcoming poverty. The withdrawal of the benefit doesn t corroborate individual is return to economic realities experienced previously, causing increased SAN/IA Mild detriment of Moderate/Severe. In addition, families who remained in the program included both times, have managed to overcome food insecurity with over the years. While that is constituted as a measure in emergency through direct income transfer, the Bolsa Família is a measure that can contribute in reducing poverty and misery in the long run. In combating food insecurity and nutrition, additional policies and programs that act on other determinants.